A Novel N of 1 Trial Design and Proposed Utility in Complementary and Alternative Medicine Research - Joshua Z. Goldenberg BA; Cynthia A. Wenner PhD (SAGE Publishing, 2012)
An N of 1 trial is a multiple crossover study in a single participant. N of 1trials can combine the benefits of individualized patient practice and evidence-based medicine and are amenable to complementary and alternative medicine practice and research. This article will review the basic structure of N of 1trials, discuss how they are commonly used, and review their limitations and statistical considerations. The authors also propose a novel use of the N of 1 trial in the form of mixed-methodology add-on N of 1 trials targeted to a parent trial's responders. This design can help uncover evidence of subgroup effects in small trials, address issues surrounding the small study effect, and explore the role of interparticipant variability and random chance in the parent trial.